O comportamento de preensão palmar em lactentes humanos - Moraes, Marcus Vinicius Marques de (2010)
The palmar grasp behavior in human infants has been approached by this work. Three studies were conducted. The first study consisted of exposing the state of the art regarding the use of palmar grasp reflex (PGR) in neuropsichomotor assessment instruments and the use of PGR as a research subject in infants. The second study determined the reliability of an instrument to measure grasp strength in infants from birth to two months old. We have studied 39 healthy infants of both sexes who were allocated into three groups ("SC", "FR", "BL") according to the city from where came from . The equipment under test was called M-FLEX , which provides values of maximum grasp strength (FMAX), mean grip force (FMEAN) and grasp time (GT). The third study aimed to characterize the palmar grasp behavior of human infants , we studied 90 healthy infants of both sexes, born at term, originated from three Brazilian cities with climate and socio-cultural characteristics similars. Infants were classified into three groups according to their age. Measurements were performed on both hands face to the right side, face in the middle line and face to the left side. The variables were compared between sexes and correlated with data weight and height development. Comparisons were made of variables between the different positions of the face and between age groups. It was found that the side that the face is turned and age group are factors that affect the variables measured by M-FLEX and it is possible to measure how much asymmetry is tolerable to characterize the behavior of an infant with typical grasp.